Analisis Pengaruh Dimensi Fraud Pentagon terhadap Kecurangan Akademik Mahasiswa Fakultas Ekonomi dengan Religiusitas sebagai Variabel Moderasi (International Forum of Researchers and Lecturers, 2023)
This study aims to examine the effect of pressure, opportunity, rationalization, competence, and arrogance on academic fraud with religiosity as a moderating variable. This research is a quantitative type. The population in this study were 521 students of the Faculty of Economics, Islamic University of Majapahit for the academic year 2019 - 2020. The sampling technique used the purposive sampling method so that a total of 190 respondents were obtained. This study uses primary data obtained from distributing questionnaires through the Google form with a measuring tool in the form of a Likert scale. The data analysis technique uses descriptive statistics with the SmartPLS data testing tool using the outer model and inner model of measurement. The results showed that pressure, opportunity, rationalization, and arrogance had a positive and significant effect on academic fraud while competence had no effect on academic fraud. Religiosity is not able to moderate the effect of pressure, opportunity, rationalization, and competence on academic fraud. Religiosity is able to moderate the effect of arrogance on academic fraud.